P3_5 I Will Blow Your House In - Gregory, Jenny; Taylor-Ashley, Jessica; Garner, Robert; Worthy, Daniel (Physics Special Topics, 2013)
The Three Little Pigs fable describes the disastrous fate of three pigs houses caused by a wolf will well-endowed lungs. This paper models the pigs houses as a simple aerofoil roof upon a house structure and discusses the wind speed required to blow the houses down. We concluded that the wind velocities to blow a straw, wood, and slate roof o are 624m/s, 861m/s and 1070m/s respectively. We then compared these to typical tornado velocities.